A Study on Customers' Expectations Towards Share Brokers - Ganapathi, R.; Ramasamy, T. (Indian Journal of Marketing, 2007)
The development of Indian economy is based on the effective functioning of capital market. Share brokers are playing vital role in the functioning of capital market. Capital market consists of both primary market and secondary market. The volume of secondary market is more than the volume of primary market. Therefore, a field study was conducted to find out the types of services provided and the level of satisfaction derived from the services provided by the share brokers. The investors are of many types. Like wise, the share brokers are of many types. Some investors are satisfied with the services provided by the share brokers. But, the study was conducted to find out the level of satisfaction derived by the investors out of the services provided by the share brokers. The level of satisfaction of the investors is measured with the help of five point scale i.e., excellent, very good, good, fair and poor. The types of services provided by the share brokers are classified as most important, more important, important, least important and unimportant. Some investors are following on line trading for buying and selling of shares. Therefore, these investors are expecting certain facilities in the software. These expected facilities are ranked on the basis of the weightage scores obtained by such facility. The collected primary data were also analyzed with the help of percentage. The chi-square test is also applied to find out the significant relationship between the level of satisfaction and independent variables like gender, age groups, the level of investment, share broker and the experience of share brokers. Some constructive suggestions are also given to provide best services to the investors.